Psycholinguistics of Organizational Phenomena: A Case of the Managerial Culture Study - Віталій Шимко (Психолінгвістика)
Purpose. This article is devoted to the case study of relevant linguacultural stereotypes of the particular organization’s managerial culture and based on corresponding results the inquiry of the discourses formation features associated with the lexico-semantic meanings dispersion of (Foucault).